2014
DOI: 10.1098/rstb.2013.0155
|View full text |Cite
|
Sign up to set email alerts
|

Leptin regulation of hippocampal synaptic function in health and disease

Abstract: The endocrine hormone leptin plays a key role in regulating food intake and body weight via its actions in the hypothalamus. However, leptin receptors are highly expressed in many extra-hypothalamic brain regions and evidence is growing that leptin influences many central processes including cognition. Indeed, recent studies indicate that leptin is a potential cognitive enhancer as it markedly facilitates the cellular events underlying hippocampal-dependent learning and memory, including effects on glutamate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 83 publications
1
100
0
Order By: Relevance
“…Neuroprotective properties of PRL have also been demonstrated in a kainic acid-induced rat model of epilepsy, where the administration of PRL to ovariectomised rats significantly reduced seizures and neurotoxicity in the hippocampus [118]. This is noteworthy, as recent data suggest that PRL may be a possible marker for obesity in humans [77].…”
Section: Leptin and Inflammationmentioning
confidence: 78%
See 2 more Smart Citations
“…Neuroprotective properties of PRL have also been demonstrated in a kainic acid-induced rat model of epilepsy, where the administration of PRL to ovariectomised rats significantly reduced seizures and neurotoxicity in the hippocampus [118]. This is noteworthy, as recent data suggest that PRL may be a possible marker for obesity in humans [77].…”
Section: Leptin and Inflammationmentioning
confidence: 78%
“…1). Nevertheless, the ability of Lep to regulate hippocampal synaptic function markedly declines with age, and these changes have been linked to neurodegenerative disorders such as AD [77]. In fact, it has been described that individuals with early AD, or mild cognitive impairment, show low plasma Lep levels [78].…”
Section: Leptin Functions In the Hippocampusmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the central actions of the hormone leptin are not restricted to the hypothalamus and the regulation of energy homeostasis. Indeed, a number of extrahypothalamic brain regions, including the hippocampus display high levels of leptin receptor expression (Irving and Harvey 2014). Leptin mRNA and protein are also highly expressed in the hippocampal formation (Morash et al 1999) and emerging evidence suggests brain-specific production of leptin (Eikelis et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous studies indicate that leptin has potential cognitive enhancing properties as it readily facilitates the cellular events underlying hippocampal learning and memory. Thus, leptin has rapid effects on activity-dependent synaptic plasticity, glutamate receptor trafficking and dendritic morphology (Irving and Harvey 2014). In addition, several studies have identified neuroprotective effects of leptin as the viability of central and peripheral neurons is markedly influenced by this hormone (Weng et al 2007;Doherty et al 2008;Guo et al 2008).…”
Section: Discussionmentioning
confidence: 99%